Immunohistochemistry Detection Apoptosis Related with ORF Virus Infection in Sheep Based on Caspase 3 Detection from Selected Farms in Basrah - Yasmeen Jasim Mohammed; Eman Hashim Yousif (Indian Journal of Forensic Medicine & Toxicology, 2022)
This study was designed for the molecular detect of apoptosis related with ORFV infection in sheepbased on detected caspase (3) by immunohistochemistry. The samples were taken from the skin of thelips of animals infected with contiguous ecthema. The ability of the virus to induce apoptosis was alsoverified using cellular immunohistochemistry and the use of a polyclonal anti-caspase (3) antibody todetect apoptotic activity. The results of the study revealed positive expression of caspase (3), where ahigh percentage of caspase (3) was observed in the affected cells in the epidermis of the lip, in additionto the presence of overexpression in all layers of the epidermis, with the presence of small areas ofapoptotic cells compared with the control group.